Landslide-Induced Weathering in Tectonically Active Mountains: Evidence From Dissolved Radiogenic Uranium Isotopes - Li, Laifeng; Li, Gen K.; Li, Le; Li, Gaojun (Frontiers in Earth Science, 2022)
Understanding weathering processes in landslide-dominated catchments is critical for evaluating the role of landslides in chemical weathering and the global carbon cycle. Previous studies have focused on solute concentrations in landslide-impacted landscapes, but have paid less attention to developing isotopic tracers of landslide-induced weathering fluxes. Recent work found that the dissolved radiogenic uranium isotopes in river water are closely related to the denudation rates in catchments draining steep mountains where landslides are thought to be a major erosion mechanism, suggesting the potential of uranium isotopes to trace landslide-induced weathering fluxes. Here we compile the dissolved radiogenic uranium isotopes (234U/238U ratios) in the river water samples from a group of catchments with variable landslide activities in the Minjiang River Basin at the eastern margin of the Tibetan Plateau. We derive three metrics of landslide activity from the analyses of digital topography and an inventory map of the co-seismic landslides triggered by the 2008 Mw7.9 Wenchuan earthquake: the normalized volume of landslides, the mean catchment slope angle, and the fraction of slopes steeper than a threshold angle beyond which slopes are mechanically unstable. The riverine dissolved 234U/238U ratios correlate negatively with the metrics of landslide activity in each catchment, which likely reflect the influence of landslides on the dissolved 234U/238U ratios. Mechanistically, enhanced bedrock landsliding would accelerate the exposure of fresh rock, promoting bedrock weathering and congruent dissolution of 234U and 238U contained in minerals; reduced landslide activities and enhanced regolith weathering would lead to preferential accumulation of 234U against 238U in solutes through alpha-recoil ejection, thus increasing dissolved 234U/238U. Our findings provide field evidence of using the riverine dissolved 234U/238U ratio to trace weathering fluxes driven by landslides, shedding new light on chemical weathering processes in uplifting mountains.